Reduction of oil uptake in vacuum fried Pleurotus eryngii chips via ultrasound assisted pretreatment - Ren, Aiqing; Cao, Zhenzhen; Tang, Xiaoxian; Duan, Zhenhua; Duan, Xu; Meng, Xiangyong (Frontiers in Nutrition, 2022)
The reduction of oil uptake in vacuum-fried Pleurotus eryngii chips by ultrasound assisted pretreatment was investigated regarding the pore structure changes. Pore structure of Pleurotus eryngii chips with four pretreatments, such as blanching, blanching + osmosis, blanching + ultrasound and blanching + ultrasound assisted osmosis was determined by mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM). In addition, quality of vacuum-fried Pleurotus eryngii chips such as hardness, rehydration ratio, oil content, etc. were also measured. The results showed that the oil absorption of vacuum fried Pleurotus eryngii chips was affected by the porous structure. The oil content of vacuum fried Pleurotus eryngii chips was significantly and positively correlated with the pores with diameters above 50 μm, 5 ~ 50 μm and 0.5 ~ 5 μm in the samples both before and after vacuum frying, while negatively correlated with the pores with diameters below 0.5 μm. Ultrasound treatment changed the microporous structure of Pleurotus eryngii chips, effectively hindering the oil absorption of samples. In particular, ultrasound assisted osmosis pretreatment induced the formation of more micropores. It was concluded that blanching + ultrasound assisted osmosis pretreatment is a promising method to reduce oil absorption and improve the quality of vacuum fried foods.